Найти сумму корней уравнения 4 √х+1=х^2 √х+Решить уравнение √1+3х – 1 +х =0

1. Найти сумму корней уравнения 4 √(х+1)=х^2 √(х+1).
2.Решить уравнение √(1+3х) - 1 +х =0

  • 1) 4 * V ( X + 1) = X^2 V (X + 1)
     V16* (X + 1) = V X^4*(X + 1)
    16*(X+1) = X^4*(X + 1)
    16 = X^4 
    X = 2 
    ОТВЕТ: Х = 2
    .......................................................................
    V ( 1 + 3X) = 1 - X
    V ( 1 + 3X) = V ( 1  - 2X + X^2 )
    1 + 3X = 1 - 2X + X^2
    X^2 - 5X = 0
    X*(X - 5) = 0
    X1 = 0
    X2 = 5
    ...................
    1) 1 + 3X > 0 --> 3X > ( -1) ---> X > ( -13)
    2) 1 - X > 0 ---> - X >_ ( - 1 ) ---> X < _ 1 
    ОТВЕТ: Х= 0

See also: